OPTIMALISASI NILAI AKURASI PEMOTONGAN AKRILIK BERWARNA MENGGUNAKAN CNC LASER CUTTING DIODA 15 WATT - Ramadhan, A.; Sairul Effendi; Almadora Anwar Sani (MACHINERY Jurnal Teknologi Terapan, 2025)
In this study, a 15 watt diode laser cutting was used to cut black acrylic material with a thickness of 2 mm. In cutting black acrylic, cutting parameters are required to obtain optimal cutting results, so to obtain optimal parameters, a quantitative method is used with the Larger Is Better characteristic taguchi method approach. There are 3 factors used for cutting parameters, namely laser power (%), cutting speed (mm / min) and nozzle distance (mm). The nozzle distance is a factor that has a significant effect on the results of cutting acrylic with P-Value = 0.000. The optimal cutting parameters for 2 mm acrylic thickness are laser power: 95%, cutting speed: 10 mm / min and nozzle distance: 50 mm with a cutting accuracy of 98.20%.